Colon cancer incidentally diagnosed after intestinal obstruction caused by ingested beef bones - Jeong, Woon Kyung; Baek, Seong Kyu (Korean journal of clinical oncology, 2014)
We report a case of the incidental diagnosis of an ascending colon cancer following intestinal obstruction due to ingestion of beef bones. A 75-year-old man visited the emergency room with abdominal distension and vomiting for 5 days. He had a history of consuming Korean beef bone soup seven days previously. An abdominal computed tomography scan revealed an ascending colon cancer with an impacted foreign body that was causing intestinal obstruction. On the 11th day after admission, right hemicolectomy was performed. Two bone-like materials were shown in the ascending colon and were pathologically confirmed as cortical bone fragments. The ascending colon cancer was a moderately differentiated adenocarcinoma (pT3N0M0). Surgeons should consider the possibility that colorectal cancer could be the cause of intestinal obstruction when the patient has a history of ingesting a foreign body and the foreign body lodges in the colon and rectum.